2017
DOI: 10.1038/ncomms13824
|View full text |Cite
|
Sign up to set email alerts
|

BMP restricts stemness of intestinal Lgr5+ stem cells by directly suppressing their signature genes

Abstract: The intestinal epithelium possesses a remarkable self-renewal ability, which is mediated by actively proliferating Lgr5+ stem cells. Bone morphogenetic protein (BMP) signalling represents one major counterforce that limits the hyperproliferation of intestinal epithelium, but the exact mechanism remains elusive. Here we demonstrate that epithelial BMP signalling plays an indispensable role in restricting Lgr5+ stem cell expansion to maintain intestinal homeostasis and prevent premalignant hyperproliferation on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

21
235
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 250 publications
(256 citation statements)
references
References 69 publications
21
235
0
Order By: Relevance
“…3b), though less so than in the EdU + stem cell network ( Supplementary Fig. 6), consistent with recent work demonstrating that BMP suppresses stem cell signature genes and, consequently, proliferation 10 . Perturbations targeting the Wnt pathway (Wnt, GSK3-i, PORCN-i) were highly connected in the TA cell network, more so than in the EdU + stem cell network, consistent with the observation that Wnt3a specifically upregulated TA cells ( Fig.…”
Section: Ta Cells Integrate Signals Via Cell-type-specific Patterns Osupporting
confidence: 91%
“…3b), though less so than in the EdU + stem cell network ( Supplementary Fig. 6), consistent with recent work demonstrating that BMP suppresses stem cell signature genes and, consequently, proliferation 10 . Perturbations targeting the Wnt pathway (Wnt, GSK3-i, PORCN-i) were highly connected in the TA cell network, more so than in the EdU + stem cell network, consistent with the observation that Wnt3a specifically upregulated TA cells ( Fig.…”
Section: Ta Cells Integrate Signals Via Cell-type-specific Patterns Osupporting
confidence: 91%
“…The bona fide ISC marker LGR5 is expressed exclusively at the intestinal crypt base under tight regulation, while LGR5 + ISCs are indispensable for regeneration and tumourigenesis (Metcalfe et al, 2014;de Sousa e Melo et al, 2017). Transcriptional control of LGR5 by Wnt, ASCL2 and BMP has been reported in the past (van der Flier et al, 2009;Schuijers & Clevers, 2012;Qi et al, 2017), yet the regulation of LGR5 protein turnover is largely unknown. To our knowledge, this is the first study describing the post-translational modification of LGR5 receptors via the E3 ubiquitin ligases NEDD4 and NEDD4L.…”
Section: Discussionmentioning
confidence: 99%
“…BMP signaling limits hyper-proliferation of the intestinal epithelium and maintains differentiation along the crypt-villus axis by forming a gradient of BMPactivity where mesenchymal cells beneath the crypts express high levels of noggin whereas high levels of BMP-2 and-4 are expressed by mesenchymal cells both in the crypt and the villi [25][26][27][28]. Recent evidence has also shown that BMP-signaling constrains the selfrenewal of Lgr5+ cells via SMAD-mediated repression of the stem cell signature [29]. SMAD4 expression is frequently lost in invasive colorectal cancer, indicating that the quenching of the BMP-signaling pathway in CRC tumoroids through noggin supplementation may be less essential for successful tumoroid in vitro culture [30,31].…”
Section: Discussionmentioning
confidence: 99%